The phenomenon of the conspiracy of silence in patients in palliative care: an integrative review - Machado, Juliana Costa (2018)
The objective was to identify the phenomenon of the conspiracy of silence in the experience of patients in palliative care, family and health professionals. This is an integrative review, carried out based on searches in the Virtual Health Library (VHL), firstly by means of the descriptors "Palliative Care", "Palliative Care in the terminality of life" and "Conspiracy of silence", being AND the operator boolean used. Then we used the terms "conspiracy of silence" and "pact of silence". The inclusion criteria were: year of publication, last 10 (ten) years (2008 to 2017); languages: Portuguese, English and Spanish; and text in full. Thus, 9 articles were selected, 7 (77.8%) indexed in the BDENF and 2 (22.2%) in LILACS. The results showed a high incidence of the conspiracy of silence in patients undergoing palliative care, ineffective communication contributes to the lack of information among health professionals, patients and families about the diagnosis and prognosis of the disease. Feelings of fear, anguish and anxiety are experienced by patients and family members. It is concluded that there is a need to learn to listen to patients and their families with the objective of understanding how to best communicate the communication about the terminality of life, providing autonomy to the patient in the conduct of their attitudes towards the process they are experiencing.